Constraining the budget of NOx and volatile organic compounds at a remote tropical island using multi-platform observations and WRF-Chem model simulations - C. Poraicu; J.-F. Müller; T. Stavrakou; C. Amelynck; C. Amelynck; B. W. D. Verreyken; B. W. D. Verreyken; B. W. D. Verreyken; B. W. D. Verreyken; N. Schoon; C. Vigouroux; N. Kumps; et al. (Atmospheric Chemistry and Physics)
Volatile organic compounds (VOCs) act as precursors to ozone and secondary organic aerosols, which have significant health and environmental impacts. They can also reduce the atmospheric oxidative capacity. However, their budget remains poorly quantified, especially over remote areas such as the tropical oceans. Here, we present high-resolution simulations of atmospheric composition over Réunion Island, located in the Indian Ocean, using the Weather Research and Forecasting model coupled with Chemistry (WRF-Chem). The coexistence and spatial heterogeneity of anthropogenic and biogenic emission sources in this region present a valuable but challenging test of the model performance. The WRF-Chem model is evaluated against several observational datasets, including proton transfer reaction mass spectrometry (PTR-MS) measurements of VOCs and oxygenated VOCs (OVOCs) at the Maïdo Observatory, Réunion Island (2160 m above sea level), in January and July 2019, representing austral summer and winter, respectively, and capturing the seasonal extremes for the region. While the primary goal of our study is to gain a better understanding of the (O)VOC budget at remote tropical latitudes, important model refinements have been made to improve the model performance, including the implementation of high-resolution anthropogenic and biogenic isoprene emissions, updates to the chemical mechanism, and adjustments to the boundary conditions. These refinements are supported by comparisons with PTR-MS data as well as with meteorological measurements at Maïdo; in situ NOx and O3 measurements from the air quality Atmo-Réunion network; Fourier transform infrared spectroscopy (FTIR) measurements of O3, CO, ethane, and several OVOCs, also at Maïdo; and satellite retrievals from the TROPOspheric Monitoring Instrument (TROPOMI).